2020
DOI: 10.1021/acssensors.0c00279
|View full text |Cite
|
Sign up to set email alerts
|

Bright and High-Performance Genetically Encoded Ca2+ Indicator Based on mNeonGreen Fluorescent Protein

Abstract: Genetically encodable calcium ion (Ca 2+ ) indicators (GECIs) based on green fluorescent proteins (GFP) are powerful tools for imaging of cell signaling and neural activity in model organisms. Following almost 2 decades of steady improvements in the Aequorea victoria GFP-based GCaMP series of GECIs, the performance of the most recent generation (i.e., jGCaMP7) may have reached its practical limit due to the inherent properties of GFP. In an effort to sustain the steady progression toward ever-improved GECIs, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…The conformational change of AfArsR upon binding to As 3+ was expected to alter the chromophore environment, thus changing the fluorescence emission intensity ( Figure 4 B). This topology has been previously reported for the construction of Ca 2+ , glutamate, K + , and citrate biosensors [ 26 , 29 , 30 , 31 ] among many others. We found that insertion of intact AfArsR into the GFP scaffold resulted in a prototype green fluorescent indicator, designated as GEAR-G1.…”
Section: Resultssupporting
confidence: 54%
“…The conformational change of AfArsR upon binding to As 3+ was expected to alter the chromophore environment, thus changing the fluorescence emission intensity ( Figure 4 B). This topology has been previously reported for the construction of Ca 2+ , glutamate, K + , and citrate biosensors [ 26 , 29 , 30 , 31 ] among many others. We found that insertion of intact AfArsR into the GFP scaffold resulted in a prototype green fluorescent indicator, designated as GEAR-G1.…”
Section: Resultssupporting
confidence: 54%
“…Nevertheless, locomotor activity is not a direct measurement of neural activity. Calcium sensors, such as the GCaMP series 57 , 58 , the more recently introduced GECO 59 , 60 , and CaMPARI, offer opportunity for more direct measures of neural activity. Importantly, CaMPARI provides a temporal-snapshot of neural activity in the freely swimming animal, which can be anesthetized and imaged after the experiment 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, locomotor activity is not a direct measurement of neural activity. Calcium sensors, such as the GCaMP series 57,58 , the more recently introduced GECO 59,60 , and CaMPARI, are more accurate. CaMPARI provides a temporal-snapshot of neural activity in the freely swimming animal, which can be anesthetized and imaged after the experiment 34 .…”
Section: Discussionmentioning
confidence: 99%